Substantial restoration of night vision in adult mice with congenital stationary night blindness - Juliette Varin; Nassima Bouzidi; Gregory Gauvain; Corentin Joffrois; Melissa Desrosiers; Camille Robert; Miguel Miranda De Sousa Dias; Marion Neuillé; Christelle Michiels; Marco Nassisi; José-Alain Sahel; Serge Picaud; et al. (Molecular Therapy: Methods & Clinical Development, 2021)
Complete congenital stationary night blindness (cCSNB) due to mutations in TRPM1, GRM6, GPR179, NYX, or leucine-rich repeat immunoglobulin-like transmembrane domain 3 (LRIT3) is an incurable inherited retinal disorder characterized by an ON-bipolar cell (ON-BC) defect. Since the disease is non-degenerative and stable, treatment could theoretically be administrated at any time in life, making it a promising target for gene therapy. Until now, adeno-associated virus (AAV)-mediated therapies lead to significant functional improvements only in newborn cCSNB mice. Here we aimed to restore protein localization and function in adult Lrit3−/− mice. LRIT3 localizes in the outer plexiform layer and is crucial for TRPM1 localization at the dendritic tips of ON-BCs and the electroretinogram (ERG)-b-wave. AAV2-7m8-Lrit3 intravitreal injections were performed targeting either ON-BCs, photoreceptors (PRs), or both. Protein localization of LRIT3 and TRPM1 at the rod-to-rod BC synapse, functional rescue of scotopic responses, and ON-responses detection at the ganglion cell level were achieved in a few mice when ON-BCs alone or both PRs and ON-BCs, were targeted. More importantly, a significant number of treated adult Lrit3−/− mice revealed an ERG b-wave recovery under scotopic conditions, improved optomotor responses, and on-time ON-responses at the ganglion cell level when PRs were targeted. Functional rescue was maintained for at least 4 months after treatment.